Aktualisasi Dakwah dan Implikasinya dalam Mewujudkan Masyarakat Rukun Beragama (Tinjauan Terhadap Materi Dakwah Di Kabupaten Asahan) - Rahmadi*, Fuji; Siregar, Bahtiar; Nurrayza, Nurrayza; Putri, Vinita (Universitas Syiah Kuala, 2023)
Da'wah is carried out to spread religious teachings where humans as human beings choose religion according to their respective beliefs, but the reality seen now is that religion has become a commodity and even a source of conflict and so on, therefore da'wah is expected to be one of the unifying ways so that there are not many misunderstandings between religious communities so that religious harmony can be realized properly. Da'wah is carried out to increase understanding for religious adherents and society, this is also done as a preventive measure from the entry of understanding about religion that is not true. The mission of da'wah is carried out to explain the religious teachings that he believes in with the aim that others can understand religious teachings through the da'wah delivered and can be implemented in everyday life. Asahan Regency with a majority Muslim population is also very focused on realizing the religious harmony carried out by ulama and da'i. The actualization of da'wah and its implications allegedly have a correlation with the da'wah material delivered. So it is very necessary to review the da'wah material delivered in the community to realize religious harmony in Asahan Regency. This research is a type of qualitative research that aims to describe the phenomenon of a condition in the field, this research uses purposive sampling techniques, and data collection techniques, namely observation, interviews and documentation. The results showed that (1) the actualization of da'wah is an important part that must be of concern to da'i including da'i professionalism, da'wah methods and selected da'wah materials which in principle have implications for the realization of religious harmony in Asahan Regency (2) the delivery of da'wah carried out by da'i has chosen da'wah material that is in accordance with the conditions of the community in the field such as the study of tawhid, fiqh and morals so as to arouse the spirit of religious harmony.